MENUS FOR ATHLETES - Enes Šunje (Sport Scientific And Practical Aspects, 2025)
Nutrition for athletes and making of menus for athletes plays a major role in professional sports and lives of recreational and amateur athletes. Implementation of a sports menu is often the predominant and determining nuance in the process of athletic preparation and athletic fitness, which results in creation of a big difference between top athletes and those who are not top athletes. Nutrition itself is the nuance in a large number of cases, because, as much as it is important to exercise it is also important how we nourish ourselves.